Labor Markets during the COVID-19 Crisis: A Preliminary View - Olivier Coibion; Yuriy Gorodnichenko; Michael Weber (Institute of Labor Economics (IZA), 2020)
We use a repeated large-scale survey of households in the Nielsen Homescan panel to characterize how labor markets are being affected by the covid-19 pandemic. We document several facts. First, job loss has been significantly larger than implied by new unemployment claims: we estimate 20 million lost jobs by April 8th, far more than jobs lost over the entire Great Recession. Second, many of those losing jobs are not actively looking to find new ones. As a result, we estimate the rise in the unemployment rate over the corresponding period to be surprisingly small, only about 2 percentage points. Third, participation in the labor force has declined by 7 percentage points, an unparalleled fall that dwarfs the three percentage point cumulative decline that occurred from 2008 to 2016. Early retirement almost fully explains the drop in labor force participation both for those survey participants previously employed and those previously looking for work.
Keywords: E31; C83; D84; J21; J26; 330; labor market; unemployment; employment; COVID-19